The walking drum [compact disc, unabridged] - L'Amour, Louis, 1908-1988 (Random House Audio, 2010)
Warrior, lover, and scholar, Kerbouchard boldly sweeps through the castles, villages, and galleys of twelfth-century Europe, in an adventure that takes him from the shores of Brittany to the steppes of Russia.